2014
DOI: 10.1007/s10111-014-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

An approach to collaborative learning and the serious game development

Abstract: This paper presents the overall learning process that evolved during the MASCA project (MAnaging System Change in Aviation-EU FP7 funded project (2010-2013), specifically focusing on the one of the key elements of the overall learning approach, the development of a Serious Game (SKYBOARD) and the role the game played in supporting the implementation of Airport Collaborative Decision Making (A-CDM) in a major European airport. The underlying principles of the learning process was based on ongoing and collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…Through this process, fundamental learning about water resources took place, emphasizing soft skills, including critical thinking, problem solving, collaborative (team) learning, and time management. Several studies that have looked at the effects of collaborative learning in serious game development (Corrigan et al, 2015;Prensky, 2003;Mansour and El-Said, 2008) found that the development of serious games (within the workplace, Corrigan et al, 2015) play a role in fostering the development and improvement of various soft skills, such as communication, collaboration, or negotiation, and enhance overall collaborative learning, similar to learning outcomes from playing serious games. Corrigan et al (2015) further suggest that "we are at the beginning of a fundamental shift in the way both learning and working is happening in organisations", and that these novel, active learning tools, including both playing and developing serious games, can add a critical collaborative dimension to decision making that cannot be learned otherwise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through this process, fundamental learning about water resources took place, emphasizing soft skills, including critical thinking, problem solving, collaborative (team) learning, and time management. Several studies that have looked at the effects of collaborative learning in serious game development (Corrigan et al, 2015;Prensky, 2003;Mansour and El-Said, 2008) found that the development of serious games (within the workplace, Corrigan et al, 2015) play a role in fostering the development and improvement of various soft skills, such as communication, collaboration, or negotiation, and enhance overall collaborative learning, similar to learning outcomes from playing serious games. Corrigan et al (2015) further suggest that "we are at the beginning of a fundamental shift in the way both learning and working is happening in organisations", and that these novel, active learning tools, including both playing and developing serious games, can add a critical collaborative dimension to decision making that cannot be learned otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that have looked at the effects of collaborative learning in serious game development (Corrigan et al, 2015;Prensky, 2003;Mansour and El-Said, 2008) found that the development of serious games (within the workplace, Corrigan et al, 2015) play a role in fostering the development and improvement of various soft skills, such as communication, collaboration, or negotiation, and enhance overall collaborative learning, similar to learning outcomes from playing serious games. Corrigan et al (2015) further suggest that "we are at the beginning of a fundamental shift in the way both learning and working is happening in organisations", and that these novel, active learning tools, including both playing and developing serious games, can add a critical collaborative dimension to decision making that cannot be learned otherwise. Our course was a first step in testing se-rious game development in the classroom and further insight into the learning outcomes as well as carry-on effects into the workplace would be an interesting research question that could shed light on whether just playing games (emphasizing the fun factor) might be enough to achieve similar learning effects to the full process of game development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Williams, Kapralos, Hogue, Murphy, & Weckman, 2014) authors presented a simulation for training of fire service, which it was intended to take advantage of interactive techniques, innovative and the attractive immersion provided by the serious games. (Corrigan et al, 2015) carried out a study for change management in the aviation system in European Union. This work developed a game in an important European airport to support the implementation of an airport collaborative decision-making (A-CDM).…”
Section: E-learningmentioning
confidence: 99%
“…The basic principles that are worked are the implementation of game mechanics, the continuous learning and collaboration in the working place according (Corrigan, Zon, Maij, McDonald, & Mårtensson, 2015). These elements are fundamental role because learning and work converge in the organization management.…”
Section: Introductionmentioning
confidence: 99%